Pengaruh Disiplin Belajar dan Lingkungan Teman Sebaya Terhadap Prestasi Belajar Pada Mata Pelajaran Produktif Siswa Jurusan Pemasaran SMK Negeri 3 Surakarta - Ningrum, Dita Oktavia; Adi, Bambang Wasito; sudarno, Sudarno (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2019)
The research aims to know; (1) the effect of learning discipline and peer environment on learning achievement in productive subjects of marketing major students in 3rd Vocational High School Surakarta; (2) the effect of learning discipline on learning achievement in productive subjects of marketing major students in 3rd Vocational High School Surakarta; (3) the effect of peer environment on learning achievement in productive subjects of marketing major students in 3rd Vocational High School Surakarta. This type of research is quantitative research with descriptive methods. The population of this research was all students of class XI Majors in Marketing of VHS 3 Surakarta. The selected research sample of 84 students consisting of classes XI Marketing 1, XI Marketing 2, XI Marekting 3. The samples were taken by using proportionate random sampling. The data collection using questionnaires for leraning discipline and peer environment variables, while documentation is used to get data on learning achievement. Those data were analyzed by using the correlation and multiple regression statistical techniques. The result of this research are as follows. First, learning discipline and peer environment has a positive and significant effect on learning achievement in productive subjects of marketing major students in 3rd Vocational High School Surakarta as indicated by the value of Fstat 14,233 > Ftable 3,11. Second, learning discipline has a positive and significant effect on learning achievement in productive subjects of marketing major students in 3rd Vocational High School Surakarta as shown by the value of t stat 3,208 > t table 1,989. Third, peer environment has a positive and significant effect on learning achievement in productive subjects of marketing major students in 3rd Vocational High School Surakarta as indicated by the value of t stat 2,491 > t table 1,989